Cross-border collaboration, communication, and research frontiers on biologics in chronic rhinosinusitis from 2004 to 2023 - Huang, Guan-Jiang; Fan, Zhi-Jun; Lu, Biao-Qing (Frontiers in Big Data, 2024)
ObjectiveBiologics are considered as a promising novel treatment option for patients with chronic rhinosinusitis who failed with the standard of care (medical therapy and surgical interventions). This bibliometric analysis was performed to explore cross-border collaboration, communication, and research frontiers on biologics in chronic rhinosinusitis.MethodsOriginal research publications on biologics in chronic rhinosinusitis were retrieved from the Science Citation Index-Expanded (SCI-E) database in the Web of Science Core Collection between 2004 and 2023. Using CiteSpace and R software, the country/region, author, institution, journal, reference, and keywords were extracted to analyze the research focus and global trends in this field.ResultsResearch articles exhibited a consistent rising trend from 2004 to 2023, especially the period between 2020 and 2023. Most articles were published by authors from the USA. The USA was the most cited country, enjoying the most active cooperation with other countries/regions. Bachert C owned the most publications and collaborations. Ghent University and Karolinska Institute had the most collaborations with other institutions. Journal of Allergy and Clinical Immunology and Allergy published the most articles and were the most co-cited journals. Research frontiers on biologics in chronic rhinosinusitis would focus on efficacy, quality of life, safety, children, management, etc.ConclusionsThis bibliometric analysis displayed the overall situation and global trend on biologics in chronic rhinosinusitis. The visualization analysis of publications could assist researchers rapidly in understanding the hotspots and trends. Further research is warranted to determine the long-term effects and side effects of biologics in chronic rhinosinusitis.